Instructional Approaches in Physical Fitness Course: in Case of Higher Education - Gashu Walle, Demisse (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2023)
Physical fitness, as a specific field in higher education which require special approaches, in addition to educational methods, in the instructional process. The goal of this review is to point out the importance and role of pedagogical methods and sports training approaches in instruction of physical fitness. The practice approach is considered the most important as most tasks are completed through practice, while the living words approach and demonstration approach are used more during the early learning. In addition, approaches from sports training (standard repetition training approaches, modified exercise approaches) also play an important role. Original longitudinal research offers greater opportunities to discover new scientific laws, which is recommended for future researchers on this topic.